1999
DOI: 10.1006/viro.1998.9501
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the Newcastle Disease Virus Hemagglutinin–Neuraminidase Protein That Interfere with Its Ability to Interact with the Homologous F Protein in the Promotion of Fusion

Abstract: Recent evidence suggests that the attachment (HN) and fusion (F) glycoproteins of Newcastle disease virus interact at the cell surface in a virus-specific manner to promote syncytium formation. Consistent with the existence of such an interaction, we have shown that it is possible to coimmunoprecipitate (co-IP) the two proteins from the surface of transiently expressing cells using a monoclonal antibody to either protein. Further, we show that a point mutation in the globular domain of HN that abolishes its re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 43 publications
7
90
1
Order By: Relevance
“…Our laboratory has shown that attachment-deficient NDV-AV HN, carrying substitutions for the catalytic aspartic acid, D198, is also fusion deficient and fails to interact with F at the cell surface in coimmunoprecipitation assays (4). This result is consistent with a mechanism for fusion in which receptor recognition by the globular domain of HN is the trigger for the HN-F interaction and fusion (17).…”
supporting
confidence: 60%
See 4 more Smart Citations
“…Our laboratory has shown that attachment-deficient NDV-AV HN, carrying substitutions for the catalytic aspartic acid, D198, is also fusion deficient and fails to interact with F at the cell surface in coimmunoprecipitation assays (4). This result is consistent with a mechanism for fusion in which receptor recognition by the globular domain of HN is the trigger for the HN-F interaction and fusion (17).…”
supporting
confidence: 60%
“…HN-expressing monolayers were incubated for 30 min at 4°C with a 2% suspension of erythrocytes in phosphate-buffered saline (PBS) supplemented with 1% CaCl 2 and MgCl 2 . After extensive washing, adsorbed erythrocytes were lysed in 50 mM NH 4 Cl and the lysate was clarified by centrifugation. HAd activity was quantitated by measuring the absorbance at 540 nm minus the background obtained with vector-expressing cells.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations